1950
DOI: 10.1111/j.1365-2621.1950.tb16723.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Food Plants of Central America. Viii. Guatemala

Abstract: A description of the procedure followed in the collection and preparation of samples for shipment, and an outline of the information recorded on the accompanying data sheets, were given in the first report of this series. Kodachromes were taken in duplicate of all samples, as has been done throughout the study; one set to be kept on file a t the Escuela Agricola Panamericana and the other in the M. I. T. Nutritional Biochemistry Laboratories. Specimens were also taken for the herbarium at the Escuela.Methods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1958
1958
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…None of the species tested and presented here approached the previously published ascorbic acid mínimums for M. punicifolia L., M. glabra L., or M. souzae. However, Munsell et al (38,39) reported that M. glabra L. from Guatemala yielded 14.9 and 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the species tested and presented here approached the previously published ascorbic acid mínimums for M. punicifolia L., M. glabra L., or M. souzae. However, Munsell et al (38,39) reported that M. glabra L. from Guatemala yielded 14.9 and 15.…”
Section: Discussionmentioning
confidence: 99%
“…Since the reporting of the high ascorbic acid content of the West Indian Cherry by Asenjo and Freiré de Guzman (4) z , and verification by Mustard (40), literature search indicates that Malpighia punicifolia L. (1,2,3,5,6,7,8,9,10,14,15,16,17,19,20,21,22,24,25,26,27,28,29,32,33,34,35,41,42,44,45) and the closely allied species, M. glabra L. (15,16,23,30,31,32,33,38,39,40,45,46,47) have received much attention.…”
Section: Introductionmentioning
confidence: 99%